Women from Athens: photograph, subtitles and the projection of identities in sports journalism - Almeida, Ricardo Luiz Teixeira de (Laboratório Editorial FCL-UNESP, 2008)
Critical analysis of the column “Mulheres de Atenas”, published in the sports section of the newspaper O Dia in August 15th, 2004, with an emphasis on the construction of its readers as members of a hegemonic and essentialized masculinity. The textual genre presented in “Mulheres de Atenas”, which became a fixed column in the sports section of O Dia during the Olympic Games, is that of the photograph followed by a brief explanatory written text, being thus a multimodal text par excellence, in which the combination of the image of the female body displayed by the photograph with the lexical choices of the written text seems to represent women as merchandise, while seeking to establish empathy with a reader ideally projected as man, heterosexual and “consumer” in the market of sexualrelations.